Physics, Principles & problems / Paul W. Zitzewitz - Zitzewitz, Paul W. (United States of América: Merrill Publishing Company)
Physics, a mathematical science, physics, the search for understanding, measurement and scientific methods; Mathematical relationships, graphing data, linear relationships, parabolic relationships; graphical analysis of motion, position and distance, average and instantaneous speed, velocity of velocity; forces, newton´s first law of motion, newton´s second lewof motion, te unit of force; vectors, addition, graphical method, vector addition in two dimensions, independence of vector quantities; motion in two dimensions, independence of motion in two, dimensions, projectile motion; universal gravitation, kepler´s lew of planetary motion, universal gravitation, newton´s test of the inverse square; momentum and its conservation, momentum and impulse, newton´sthird law and momentum,law of conservation of momentum; work, energy, and simple machines, work, and direction of force, energy and power, simple machine; energy, forms of energy, work and change in kinetic energy, potential energy; thermal energy, theories, hot and cold, thermal energy and temperature, equilibrium and thermomentry; gas laws, assumptions of the kinetic, molecular, theory, pressure, boyle´s law, chales´law; states of matter, fluids at rest, hydrostatics, fluids in motion, hydrodynamics; waves and energy transfer, types of waves, frequency, wavelength, and velocity, amplitude of a wave; Sound, sound waves, the doppler shift, pitch and loudness, sources of sound; light, the facts of light, the speed of light, sources of light; Reflection and refraction; mirrors and lenses; diffraction and interference of light; static electric field; current electricity; series and parallel circuits; magnetic fields; electromagnetic induction; electric and magnetic fields; quantum theory; the atom; the nucleur, nuclear applications.
Table of contents, ilustratyn diagramaty appendix
Col. Educ
Keywords: 1. FISICA 2. MATHEMATICS SCIENCE 3. GRAPHICAL ANALYSIS 4. EDUCATIÓN